Tumour necrosis factor-α in nasal allergy - K. Hisamatsu; T. Ganbo; T. Nakazawa; T. Nakajima; J. Ko; R. Goto; Y. Murakami; K. Misui (Mediators of Inflammation)
Tumour necrosis factor-α (TNF-α) was measured by enzyme-linked immunosorbent assay and eosinophil cationic protein (ECP) by radio-immunoassay to evaluate TNF-α in nasal allergy. There was no significant difference either between the mean concentrations of TNF-α in nasal secretions from the patients with perennial nasal allergy and those of normal subjects, or between the TNF-α and ECP concentrations. However, reverse transcription polymerase chain reaction showed a specific increase of TNF-α mRNA and IFN-γ mRNA in allergic nasal mucosa after allergen challenge in vitro. These findings suggest a possibility that T cell-derived IFN-γ up-regulates macrophages to elaborate TNF-α, which may play a role in amplifying allergic inflammation in the nose through the cytokine network.